2017
DOI: 10.1007/s11120-017-0416-5
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of chlorophyll triplet states by carotenoids in algal light-harvesting complexes related to fucoxanthin-chlorophyll protein

Abstract: We have used time-resolved absorption and fluorescence spectroscopy with nanosecond resolution to study triplet energy transfer from chlorophylls to carotenoids in a protective process that prevents the formation of reactive singlet oxygen. The light-harvesting complexes studied were isolated from Chromera velia, belonging to a group Alveolata, and Xanthonema debile and Nannochloropsis oceanica, both from Stramenopiles. All three light-harvesting complexes are related to fucoxanthin-chlorophyll protein, but co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…5B). These pigments enhance the lightharvesting capacity in the blue-green region and enable efficient NPQ in diatoms as an adaptation to high-light conditions (44,45). Fxs in FCPs are arranged in close proximity to Chls, forming a complementary network for photon capturing and energy transfer (27,(46)(47)(48)(49).…”
Section: Carotenoid Arrangement and Possible Adaption Mechanismsmentioning
confidence: 99%
“…5B). These pigments enhance the lightharvesting capacity in the blue-green region and enable efficient NPQ in diatoms as an adaptation to high-light conditions (44,45). Fxs in FCPs are arranged in close proximity to Chls, forming a complementary network for photon capturing and energy transfer (27,(46)(47)(48)(49).…”
Section: Carotenoid Arrangement and Possible Adaption Mechanismsmentioning
confidence: 99%
“…The relatively high ΦPSII and relatively low NPQ in HY at 74 DAT showed that the HY could maintain high PSII activity in the later stage of senescence. The decline in F0' was considered to reflect the heat dissipation of the PSII antennae depending on the xanthophyll cycle (Khoroshyy et al 2018). The gradual decrease in F0' in HY and its parents was in line with the increase in Z and DES, which further showed that antenna heat dissipation, depending on Table 3.…”
Section: Discussionmentioning
confidence: 91%
“…Carotenoids from several marine organisms such as microalgae and diatoms are considered and have previously been shown to possess excellent anti-oxidant properties [14,16,24]. Marine carotenoids sources confer with numerous advantages viz., low cost, easy availability, high chemotherapeutic and nutritional index, and low contamination due to their halophilic habitats [40].…”
Section: Discussionmentioning
confidence: 99%
“…Since its over-consumption has not been known to cause any toxicity, it has been approved and widely marketed by the United States Food and Drug Administration as a dietary supplement [22,23]. Fucoxanthin, on the other hand, characterized by its distinctively strong orange tint and commonly found in Phaeophyceae and Bacillariophyta , has also been shown to possess similar therapeutic properties [24,25]. However, it was found to be unstable and easily degraded by light, heat, and oxygen [26].…”
Section: Introductionmentioning
confidence: 99%